7 - Book Reviews: Continuity and Change in Nigerian Foreign Policy by Paul P Izah (Ahmadu Bello University Press) 1991, 153 pp.: by John Amfaņi Ayam - John Amfaņi Ayam, (Africa Development, 1993)
Abstract